2017
DOI: 10.1016/j.celrep.2017.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Diverging mRNA and Protein Networks in Activated Microglia Reveal SRSF3 Suppresses Translation of Highly Upregulated Innate Immune Transcripts

Abstract: Uncontrolled microglial activation may lead to the development of inflammation-induced brain damage. Here, we uncover a ribosome-based mechanism/checkpoint involved in control of the innate immune response and microglial activation. Using an in vivo model system for analysis of the dynamic translational state of microglial ribosomes, with mRNAs as input and newly synthesized peptides as an output, we find a marked dissociation of microglia mRNA and protein networks following innate immune challenge. Highly upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 49 publications
4
81
0
Order By: Relevance
“…Interestingly, single‐cell RNAseq has been shown, depending on the analysis depth, to detect only abundant transcripts (Peterson et al , ). Several transcripts and proteins of the DAM did not overlap (Keren‐Shaul et al , ; Mrdjen et al , ), while a marked dissociation of mRNA and protein networks was described in microglia exposed to LPS challenge (Boutej et al , ). It should be noted also, on a positive note, that mass cytometry data could be useful for instructing isolation procedures, through the identification of cell surface markers that can be used (Mrdjen et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, single‐cell RNAseq has been shown, depending on the analysis depth, to detect only abundant transcripts (Peterson et al , ). Several transcripts and proteins of the DAM did not overlap (Keren‐Shaul et al , ; Mrdjen et al , ), while a marked dissociation of mRNA and protein networks was described in microglia exposed to LPS challenge (Boutej et al , ). It should be noted also, on a positive note, that mass cytometry data could be useful for instructing isolation procedures, through the identification of cell surface markers that can be used (Mrdjen et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of cytoplasmic TDP-43 misaccumulation on mRNA translation in vivo has remained unknown. Here we used a Ribotag method (24) in combination with mass spectrometry to study the translational pro les of neurons in one-year old transgenic mice expressing ALS-linked hTDP-43 A315T mutant, a model of ALS/FTD (12). Our study revealed for the rst time that TDP-43 proteinopathy can cause translational deregulation of speci c mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…TRAP protocol described by Heiman and colleagues with small modi cations was used for the study (23,24). Cortex and hippocampal tissue were extracted from the brain and homogenized (10% w/v) together in tissue lysis buffer.…”
Section: Trap Protocolmentioning
confidence: 99%
“…While these processes have been widely studied in other cell-types, it has recently become apparent that astrocytes also must have substantial cytoplasmic posttranscriptional regulation: for example, a set of mRNAs enriched on ribosomes in peripheral astrocyte processes(PAPs) have been defined, consistent with sequence-regulated local translation 5 . Likewise, there are clear examples of posttranscriptional regulation, via expression of specific cytoplasmic RBPs, being an essential aspect of differentiation and maturation of neurons 6 , microglia 7 , and oligodendrocytes 8 . However, aside from elegant work on the Fragile X Mental Retardation Protein(FMRP) 9,10 , post-transcriptional regulators of such processes in astrocytes largely remain unknown.…”
Section: Introductionmentioning
confidence: 99%